City Branding, Electronic Word-of-Mouth, and City Image in Shaping Tourists’ Visiting Decisions - Ferry Satria; Haryadi Haryadi; Syahmardi Yacob; Junaidi Junaidi (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine how city branding and electronic Word-of-Mouth (e-WOM) influence tourists’ visiting decisions through the mediating role of city image in a medium-sized emerging tourism city. Research Methodology: This study was conducted in Sungai Penuh City, Indonesia, using a quantitative survey of 360 tourists who had previously visited the city. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS, and mediation effects were tested through bootstrapping. Results: The findings show that city branding and e-WOM have significant positive effects on both the city image and tourists’ visiting decisions. City image also has a strong direct influence on visiting decisions and significantly mediates the relationship between city branding, e-WOM, and visiting decisions. Conclusions: This study concludes that tourists’ visiting decisions in emerging urban destinations are shaped not only by institutional branding strategies and online narratives but also by how these factors are translated into a favorable city image. Limitations: This study was limited to one medium-sized tourist city and employed a cross-sectional design, which may restrict the generalizability of the results to other destinations. Contributions: This study highlights the city image as a key mechanism linking city branding and e-WOM to tourists’ visiting decisions and provides practical implications for destination managers to strengthen branding strategies and manage digital communication.